2015
DOI: 10.1093/jme/tju016
|View full text |Cite
|
Sign up to set email alerts
|

Mom Matters: Diapause Characteristics of Culex pipiens-Culex quinquefasciatus (Diptera: Culicidae) Hybrid Mosquitoes

Abstract: Females of the northern house mosquito, Culex pipiens L., are capable of entering an adult overwintering diapause characterized by arrested ovarian development, enhanced stress tolerance, and elevated lipid stores. In contrast, the southern house mosquito, Culex quinquefasciatus Say, lacks this capacity and is therefore unable to survive the harsh winters found in northern regions of North America. These two species are capable of forming fertile hybrids in the United States, yet the diapause characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…Lipid content from five female mosquitoes per dsRNA treatment and rearing condition were measured as described elsewhere (Van Handel, 1985) with slight modifications that enabled rapid measurement of lipid content in multiple samples using a plate reader (Meuti et al, 2015). Females were individually assessed as being in a diapause state if they had a lipid content >30 μg mg −1 fresh mass.…”
Section: Assessing the Diapause Status Of Dsrna-treated Mosquitoesmentioning
confidence: 99%
“…Lipid content from five female mosquitoes per dsRNA treatment and rearing condition were measured as described elsewhere (Van Handel, 1985) with slight modifications that enabled rapid measurement of lipid content in multiple samples using a plate reader (Meuti et al, 2015). Females were individually assessed as being in a diapause state if they had a lipid content >30 μg mg −1 fresh mass.…”
Section: Assessing the Diapause Status Of Dsrna-treated Mosquitoesmentioning
confidence: 99%
“…Diapause is an alternative life history strategy and a physiologically dynamic developmental pathway coordinated by a suite of neuroendocrine and metabolic controls ( Denlinger 2002 ). Many studies of the synchrony between seasonal events and insect life histories have focused on insect diapause; however, molecular regulation of diapause remains largely unknown because of the complexity of the diapause phenotype ( Meuti et al 2001 ; Kostál et al 2009 ; Ikeno et al 2010 , 2011 ; Kankare et al 2010 ; MacRae 2010 ; Yamada and Yamamoto 2011 ). Moreover, diapause is an alternative, dynamic pathway to normal active development, with various phases and modules ( Kostál 2006 ; Emerson et al 2009 ).…”
mentioning
confidence: 99%
“…In the Asian corn borer Ostrinia furnacalis the duration of diapause is also equally infl uenced by each parent, but the induction of diapause is mainly determined by paternal genes . It is also important to remember that the results of reciprocal crosses can be determined not only by the relative importance of maternal and paternal genotypes but also by epigenetic maternal effects (Denlinger, 2002;Saunders et al, 2002;Saunders, 2010;Meuti et al, 2015). Our study revealed a high level of heterogeneity in the invasive population.…”
Section: Discussionmentioning
confidence: 72%